Islamic Health System and Prevention of Contemporary Psychological and Mental Disorders: اسلامی نظام صحت کی روشنی میں معاصر نفسیاتی اور ذہنی امراض کا تدارک (Al-Mithaq ( Research Journal of Islamic Theology), 2023)
The Islamic health system, rooted in the teachings of the Qur'ān and Sunnah, is a comprehensive framework encompassing medical practices and ethical principles. The Prophet Muḥammad (ﷺ) himself exemplified the treatment of ailments and encouraged his followers to follow suit. Islam, as a way of life, provides a holistic code of conduct, ethical guidelines, and social values that contribute to the alleviation of various mental and psychological disorders. The Qur'ān, revealed by Allah, contains a complete guide to medication, and the Prophet's teachings emphasize the adoption of the Islamic Ṭibb health system as a natural approach to healing. This research article aims to shed light on the Islamic health system, particularly in addressing mental and psychological challenges prevalent in contemporary society. By adhering to Islamic Shar‘iah and Sunnah, the potential exists to mitigate mental illnesses, given the profound influence of Islamic teachings as a crucial psycho-social factor, particularly in countries with a Muslim majority. Recognizing the efficacy of Islamic Shar‘iah in the treatment of psychological issues is imperative. The article explores preventive measures against these disorders within the framework of Islamic spirituality and traditional practices, acknowledging the symbiotic relationship between religion and spirituality. By examining the Islamic perspective on mental and psychological well-being, this research contributes to the broader understanding of holistic health within the Islamic context.